DNA Primer Extension with Cyclopropenylated 7‐Deaza‐2′‐deoxyadenosine and Efficient Bioorthogonal Labeling in Vitro and in Living Cells. (15th August 2018) - Ploschik, Damian; Rönicke, Franziska; Beike, Hanna; Strasser, Ralf; Wagenknecht, Hans‐Achim
Abstract: A deoxyadenosine triphosphate (dATP) analogue for DNA labeling was synthesized with the 1‐methylcyclopropene (1MCP) group at the 7‐position of 7‐deaza‐2′‐deoxyadenosine and applied for primer extension experiments. The real‐time kinetic data reveals that this 1MCP‐modified dATP analogue is incorporated into DNA much faster than that of the similarly 1MCP‐modified deoxyuridine triphosphate (dUTP) analogue. The postsynthetic fluorescent labeling of these oligonucleotides works efficiently according to PAGE analysis, and can be applied for immobilization of a functional antibody on a surface. Site‐specific labeling at two different positions in DNA was achieved and the bioorthogonality of the postsynthetic fluorescent labeling was demonstrated in living HeLa cells. Abstract : Label making : A deoxyadenosine triphosphate analogue for DNA labeling was synthesized with the 1‐methylcyclopropene (1MCP) group at the 7‐position of 7‐deaza‐2′‐deoxyadenosine, and applied for primer extension experiments. The incorporation of bioorthogonally reactive 1MCP into DNA can be followed in real time and inside living HeLa cells.